1997
DOI: 10.4319/lo.1997.42.3.0405
|View full text |Cite
|
Sign up to set email alerts
|

Iron and grazing constraints on primary production in the central equatorial Pacific: An EqPac synthesis

Abstract: Recent studies in the central equatorial Pacific allow a comprehensive assessment of phytoplankton regulation in a high-nutrient, low-chlorophyll (HNLC) ecosystem. Elemental iron enters the euphotic zone principally via upwelling and is present at concentrations (530 PM) well below the estimated half-saturation constant (120 PM) for the large cells that bloom with iron enrichment. In addition, the meridional trend in quantum yield of photosynthesis suggests that even the dominant small phytoplankton are held b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
231
3
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(265 citation statements)
references
References 80 publications
26
231
3
1
Order By: Relevance
“…As a response to nutrient-enriched conditions during the PSM, the phytoplankton community existing in the OSM in the inshore locations shifts to a greater dominance of larger individuals, particularly diatoms (Landry et al, 1997). This was found to be true during the present study also since a pronounced enhancement of phytoplankton abundance was found in the inshore waters during the PSM period.…”
Section: Response Of Phytoplanktonsupporting
confidence: 67%
“…As a response to nutrient-enriched conditions during the PSM, the phytoplankton community existing in the OSM in the inshore locations shifts to a greater dominance of larger individuals, particularly diatoms (Landry et al, 1997). This was found to be true during the present study also since a pronounced enhancement of phytoplankton abundance was found in the inshore waters during the PSM period.…”
Section: Response Of Phytoplanktonsupporting
confidence: 67%
“…There is, of course, no puzzle about how the pico-and nanophytoplankton are held to low concentrations despite high speci"c growth rates. E$cient grazing by protozoan zooplankton keep growth and loss iǹ balancea as de"ned by Landry et al (1997). The growth rate of micrograzers and, hence, the grazing rate were coupled to the growth rate of the small phytoplankton during all seasons in the Arabian Sea (Landry et al,1998;Brown et al, 1999;Caron and Dennett, 1999).…”
Section: Regulation Of Primary Productivitymentioning
confidence: 99%
“…Large phytoplankton are also thought to be controlled at low densities by the grazing of large, generalized grazers, such as copepods, whose populations are sustained by their ability to graze on smaller phytoplankton and zooplankton size classes. The result is a system in which size classes (particularly smaller size classes) are each limited by predation (i.e., they are controlled ''top down''), whereas total phytoplankton biomass is controlled through the scarcity of iron (''bottom-up'' control), leading to ''grazer-controlled phytoplankton populations in an iron-limited ecosystem'' (Price et al 1994; see also Armstrong 1994 andLandry et al 1997).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In this scenario, resident (smallcelled) populations are kept in check by the grazing of microzooplankton (Banse 1990;Miller et al 1991;Coale et al 1996;Landry et al 1997). Larger phytoplankton species are thought to be more susceptible to iron limitation because of their smaller surface/volume ratios (Hudson and Morel 1990;Morel et al 1991;Price et al 1991;Sunda and Huntsman 1997).…”
Section: Acknowledgmentsmentioning
confidence: 99%